Pengaruh belanja modal, pertumbuhan penduduk dan investasi terhadap PDRB di Provinsi Jambi Tahun 2000-2019 (pendekatan error corection model) - Sieskawati, Wulandari; Hodijah, Siti (Jurnal Paradigma Ekonomika, 2024)
This study aims to analyze the development of Gross Regional Domestic Product, Capital Expenditure, Population Growth and Investment in Jambi Province in 2000-2019, analyze the Effect of Capital Expenditure, Population Growth and Investment on Gross Regional Domestic Product in Jambi Province in 2000-2019. The data used in this study is secondary data with the type of Time series 2000-2019 data originating from the Central Statistics Agency. This study uses the Error Correction Model Analysis, and by using the E-Views 8.0 tool. The research variable is stationary in the second difference test, then the long-term estimation shows that the variables of capital expenditure, population growth and investment have a significant effect on gross regional domestic product. While the results of the short-term estimation of capital expenditure and investment variables have a significant effect on gross regional domestic product, but population growth does not have a significant effect on gross regional domestic product, this is because in the short term new born residents and new residents have not carried out economic activities in new places so they do not affect the gross regional domestic product in the short run.